Rock fragmentation by blasting : Fragblast 10 : proceedings of the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 26-29 November, 2012 /: Fragblast 10 : proceedings of the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 26-29 November, 2012. (©2013) - Unknown
No abstract available